Dating apps and risky sexual behaviors among young adults in large cities in Indonesia - Poerwandari, Elizabeth Kristi; Berliana, Cintia (UI Scholars Hub, 2022)
Online dating applications are frequently used by young adults across the globe. Research from several countries has found a strong link between the use of dating apps and risky sexual behavior. Risky sexual behaviors refer to sexual behaviors that may lead to sexually transmitted infections (STIs) and/or unwanted pregnancies. This study aims to examine the use of smartphone dating applications by young adults in big cities in Indonesia to explore if users engage in risky sexual behavior with fellow users. To investigate this question, this study employed mixed methods including a survey and focused interviews. The survey succeeded in collecting data from 633 dating application users and the focused interviews were conducted with 6 participants. Interview participants were young adults who used dating apps and have had sexual relations with partners found through these apps. Research findings show results that are relatively similar to previous research. The results highlighted that dating app was used to find friends or partners and as a means of channeling sexual desire. On one hand, participants were aware of the consequences of the practice of unprotected sex with multiple partners. On the other hand, they expressed a preference for engaging in risky sexual behaviors rather than refraining from them, with various justified and rationalized reasons that they were quite safe. Moreover, this study also noted the instance of men committing sexual violations against women who were made vulnerable and become “trapped” as victims of a sexual offense.